Insights into the chili phytochemicals, bioactive components, and antioxidant activity of instant premixes (green and red chilies) and their reconstitution products - Monisha Arya; Priyanka Kumari; Gyanendra Kumar; Attar Singh Chauhan; Parvatam Giridhar (Food Production, Processing and Nutrition, 2024)
Abstract Chili fruits are a potential source of phytochemicals and nutrients for food and reconstituted products. Due to its high nutritional and bioactive components, the current study focused on developing chili instant food products employing hot-air drying method. The effect of the hot-air drying method on physicochemical properties, microbiological quality, retention of bioactive components, phytochemicals, antioxidant properties, and sensory quality of green and red chilies reconstitution products were investigated. HPLC quantification unveiled that fresh red chili product had retained the highest capsaicin (2703.14 µg/g) and dihydrocapsaicin (1518 µg/g) content on the 0th day. Furthermore, UPLC-MS confirmed the presence of eleven phenolic compounds such as gallic acid, chlorogenic acid, caffeic acid, syringic acid, p-coumaric acid, protocatechuic acid, trans-cinnamic acid, ferulic acid, catechin, rutin, and quercetin. Among all, ferulic acid (382.91 µg/g) was the most abundant phenolic compound in fresh green chili products, followed by trans-cinnamic acid (73.19 µg/g) in green chili reconstituted and catechin (65.66 µg/g) in green and red chili reconstituted products. The chili products retained reasonable amounts of bioactive components and antioxidants during storage without microbial growth. The correlation analysis revealed a significant correlation between capsaicinoids, phenolic compounds, and antioxidant properties, which are linearly related in green chili products. This study offers manufacturers a cost-effective technology for producing high-quality chili-reconstituted products rich in essential nutrients and health benefits. Graphical Abstract